2010
DOI: 10.1152/ajpendo.00243.2010
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic coregulator RIP140: an update

Abstract: Fritah A, Christian M, Parker MG. The metabolic coregulator RIP140: an update. Am J Physiol Endocrinol Metab 299: E335-E340, 2010. First published June 8, 2010 doi:10.1152/ajpendo.00243.2010.-RIP140 is a transcriptional coregulator highly expressed in metabolic tissues where it has important and diverse actions. RIP140-null mice show that it plays a crucial role in the control of lipid metabolism in adipose tissue, skeletal muscle, and the liver and is essential for female fertility. RIP140 has been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 37 publications
1
66
0
1
Order By: Relevance
“…Previous data indicated that RIP140 is a ubiquitously expressed transcription factor (16). By quantitative real-time quantitative PCR (qPCR) analysis, Rip140 mRNA was detected in all the mouse tissues tested and particularly in the intestine and colon (Supplemental Figure 1A; supplemental material available online with this article; doi:10.1172/ JCI65178DS1).…”
Section: Rip140 Expression In the Intestinal Epitheliummentioning
confidence: 97%
“…Previous data indicated that RIP140 is a ubiquitously expressed transcription factor (16). By quantitative real-time quantitative PCR (qPCR) analysis, Rip140 mRNA was detected in all the mouse tissues tested and particularly in the intestine and colon (Supplemental Figure 1A; supplemental material available online with this article; doi:10.1172/ JCI65178DS1).…”
Section: Rip140 Expression In the Intestinal Epitheliummentioning
confidence: 97%
“…It has been found that RIP140 binds and represses a number of nuclear receptors, including peroxisome proliferator-activated receptors and estrogen-related receptors (17). Substantial evidence has indicated that RIP140 acts as a corepressor in adipose and skeletal muscle to control the state of adiposity (41), as well as muscle fiber types and metabolism (55).…”
Section: R380 Clenbuterol Reduces Mitochondrial Substrate Oxidationmentioning
confidence: 99%
“…Recent evidence indicates that RIP140 is a multi-functional coregulator important in regulating gene expression in metabolic tissues, specifically adipose tissue, muscle and liver [160][161][162]. Loss of RIP140 resulted in a lean phenotype, resistance to obesity and increased insulin sensitivity [160].…”
Section: Rip140mentioning
confidence: 99%